Comparison of Effectiveness of Bevacizumab Combined with Panretinal Photocoagulation versus Panretinal Photocoagulation Alone in Patients with Proliferative Diabetic Retinopathy and Diabetic Macular Edema (Journal of Medical & Health Sciences Review, 2025)
Background: In recent years, the introduction of anti-VEGF (vascular endothelial growth factor) has greatly transformed the way diabetic retinopathy is being approached. Bevacizumab is a humanized monoclonal antibody that targets VEGF-A. Recent studies have shown significant regression in retinal neo-vascularization after intravitreal anti-VEGF injection in patients with proliferative diabetic retinopathy.Objective: To compare the mean change in central macular thickness using pan-retinal photocoagulation alone versus pan-retinal photocoagulation combined with intravitreal bevacizumab in patients with proliferative diabetic retinopathy and diabetic macular oedema. Method: This Randomized controlled trial was carried out at Mughal Eye Hospital Trust, Johar Town, Lahore, Pakistan from August 2024 to January 2025. 170 eyes of 85 patients included in the study who had proliferative diabetic retinopathy along with diabetic macular oedema. Patients were divided into two groups (A and B) who were treated with pan-retinal photocoagulation(PRP) alone and PRP combined with Intravitreal bevacizumab(IVB) respectively. Optical coherence tomography(OCT) was carried out pre-procedure and 12 weeks post-procedure to compare the mean change in central macular thickness between the two groups.Results: The majority of the patients, 79 out of 170 (46.47%) were between 50 to 59 years of age, 75(44.12%) were male and 95(55.88%) were females. Moreover, the change in central macular thickness with PRP alone versus PRP combined with IVB was 82.78 ± 5.57  and  117.76 ± 7.94 µm respectively.Conclusion: This study concluded that the pan-retinal photocoagulation combined with intravitreal bevacizumab is better as compared to PRP alone in terms of mean change in central macular thickness in patients with PDR and DME.